DETECTION OF POLYCYCLIC AROMATIC HYDROCARBONS COMPOUNDS CONCENTRATIONS AND THEIR FATE IN TIGRIS RIVER WITHIN BAGHDAD CITY - IRAQ. - & et al., Khalaf (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to investigate concentrations, compositions of PAHs and to study physical and chemical water characteristic in Tigris River. This study was conducted during July 2017 to April 2018. The results showed that twelve PAHs compounds were detected in water and sediment of the river and the highest concentrations of these compounds were founded in sediment samples. Concentrations of PAHs in water samples have a ranged between (0.36µg. l-1) in wet season to (0.53µg.l-1) in dry season, while the sediment sample have a ranged between (633.23µg.kg-1) in wet season to (778.28µg.kg-1) in dry season. The origin of PAHs in water and sediment were pyrogenic depending on the ratios of Phenanthene/Anthracene, Anthacene/ (Anthacene + Phenanthene), low molecular weight/high molecular weight. According of these results, it can be concluded that the Tigris River is polluted with the PAHs, and anthropogenic activities with the largest impact on the water health and quality of the river.